Penguatan Peran Perawat Dalam Pelaksanaan Asuhan Keperawatan Melalui Pelatihan Layanan Prima - Simamora, Roymond H; Purba, Jenni Marlindawani; Bukit, Evi Karota (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2018)
Community Service aims to enable nurses to understand the concept of service (the importance of service) for the survival of the hospital business. Nurses are able to see service from the point of view of the customer (patient) and understand Nine Service Bites "namely: Access, Responsiveness, Competency, Courtesy, Reliability, Speed, Security, Tangible, Professional. Helping nurses understand effective communication so as to create a good image from the hospital in the eyes of the customer. The solution provided was Strengthening Roles to Nurses in Nursing Care Services through Excellent Sevices at the University of North Sumatra hospital. Excellent service training provided, has an impact on increasing the percentage of patient satisfaction on nursing care services. The better the perception of inpatients towards nursing services in the hospital, the lower the anxiety they experience. Follow-up Plans that will be carried out are: providing a questionnaire to measure Patient Satisfaction with nursing services, provided in the room, making a monthly evaluation schedule to oversee the continuity of post-training implementation. The response of the head of the hospital regarding the implementation of the activity was the existence of a draft Policy on Hospital Leaders concerning: Implementation of the Excellent Service SPO, Selection of Champion Prima Services in each treatment room at USU Medan hospital